Mycotoxin Fumonisin B1 Interferes Sphingolipid Metabolisms and Neural Tube Closure during Early Embryogenesis in Brown Tsaiya Ducks - Lumsangkul, Chompunut; Tso, Ko-Hua; Fan, Yang-Kwang; Chiang, Hsin-I; Ju, Jyh-Cherng (Toxins, 2021)
Fumonisin B1 (FB1) is among the most common contaminants produced by Fusarium spp. fungus from corns and animal feeds. Although FB1 has been known to cause physical or functional defects of embryos in humans and several animal species such as Syrian hamsters, rabbits, and rodents, little is known about the precise toxicity to the embryos and the underlying mechanisms have not been fully addressed. The present study aimed to investigate its developmental toxicity and potential mechanisms of action on sphingolipid metabolism in Brown Tsaiya Ducks (BTDs) embryos. We examined the effect of various FB1 dosages (0, 10, 20 and 40 µg/embryo) on BTD embryogenesis 72 h post-incubation. The sphingomyelin content of duck embryos decreased (p < 0.05) in the highest FB1-treated group (40 µg). Failure of neural tube closure was observed in treated embryos and the expression levels of a neurulation-related gene, sonic hedgehog (Shh) was abnormally decreased. The sphingolipid metabolism-related genes including N-acylsphingosine amidohydrolase 1 (ASAH1), and ceramide synthase 6 (CERS6) expressions were altered in the treated embryos compared to those in the control embryos. Apparently, FB1 have interfered sphingolipid metabolisms by inhibiting the functions of ceramide synthase and folate transporters. In conclusion, FB1-caused developmental retardation and abnormalities, such as neural tube defects in Brown Tsaiya Duck embryos, as well as are partly mediated by the disruption of sphingolipid metabolisms.